POLA ASUH ANAK PADA ANAK PERKAWINAN CAMPUR ETNIS DAYAK DAN MELAYU DI KELURAHAN KANTOR - Elisabet Nova Conala; Nuraini Asriati; Riama Al Hidayah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to determine parenting styles in mixed marriages between Dayak and Malay ethnicities in the Office Village, Delta Pawan District, Ketapang Regency. The research method used is descriptive with a qualitative research form. The data source of this research is a married couple of mixed marriages between Dayak and Malay ethnicities in the Office Village, Delta Pawan District, Ketapang Regency. Data collection techniques through interviews and documentation, while data collection tools use observation and interview guidelines, observation and documentation. The research analysis was presented in a descriptive qualitative manner using six informants, consisting of two married couples and one child from each husband and wife. The results of this study indicate that there are differences in the category of parenting towards 1) permissiveness; 2) authoritarian and 3) democratic as seen from the cultural elements of the livelihood system, religious system and social system from each parent to their child. Where there is a process of cultural domination and cultural assimilation with a complete two-way process of parenting towards a permissive, authoritarian and democratic approach to mixed marriages between Dayak and Malay ethnicities in the Office of Delta Pawan District, Ketapang Regency.Keywords: Parenting Styles, Mixed Marriages, Dayak Ethnicity, Ethnic Malay